On the road to carbon reduction in a food supply network: a complex adaptive systems perspective - Touboulic, A.; Matthews, L.; Marques, L. (Emerald, 2018)
Purpose: In acknowledging the reality of climate change, large firms have set internal and external (supplier oriented) targets to reduce their greenhouse gas (GHG) emissions. This study explores the complex processes behind the evolution and diffusion of carbon reduction strategies in supply networks. Design/methodology/approach: The research uses complex adaptive systems (CAS) as a theoretical framework and presents a single case study of a focal buying firm and its supply network in the food sector. A longitudinal and multilevel analysis is used to discuss the dynamics between the focal firm, the supply network and external environment. Findings: Rather than being a linear and controlled process of adoption-implementation-outcomes, the transition to reduce carbon in a supply network is much more dynamic, emerging as a result of a number of factors at the individual, organizational, supply network and environmental levels. Research limitations/implications: The research considers the emergence of a carbon reduction strategy in the food sector, driven by a dominant buying firm. Future research should seek to investigate the diffusion of environmental strategies more broadly and in other contexts. Practical implications: Findings from the research reveal the limits of the control that a buying firm can exert over behaviours in its network and show the positive influence of consortia initiatives on transitioning to sustainability in supply networks. Originality: CAS is a fairly novel theoretical lens for researching environmental supply network dynamics. The paper offers fresh multilevel insights into the emergent and systemic nature of the diffusion of environmental practices in supply networks.